Penertiban Penggunaan Jalan di Luar Fungsi oleh Satuan Lalulintas Kepolisian Resor Kota Padang untuk Mencegah Terjadinya Kecelakaan Lalulintas - Putra, Undra; Delmiati, Susi; A. Kana, Philips (UNES Law Review, 2023)
Article 127 paragraph (1) in conjunction with Article 128 of Law Number 22 of 2009 concerning Road Traffic and Transportation regulates the use of roads outside their functions. This research is an empirical juridical research. The role of Satlantas Polresta Padang in controlling the use of roads outside the function to prevent traffic accidents is to regulate, guide, and/or supervise. Use of public roads for personal purposes for parties must obtain permission from the Police. The consideration for granting permission to use a road for personal gain by the Police is that there are alternative roads that can be used by the public so that they do not hinder traffic activities and that there are road markings that can provide indications that the road cannot be traversed, that road use cannot be carried out by completely closing the entire body. road. Forms of law enforcement by giving warnings and making forced efforts. Not yet in the jurisdiction of the Padang Police Traffic Unit has been subject to criminal sanctions for this violation. Obstacles in controlling the use of non-functional roads to prevent traffic accidents by the Padang Traffic Police, namely the insufficient number of police personnel to supervise and control the use of non-functional roads, lack of dissemination of laws and regulations regarding criminal threats to the use of roads outside of functions. Lack of coordination and cooperation between the Police and the local government, namely RT/RW, Kelurahan, to the Government of each sub-district within the city of Padang in this case, concrete actions taken by RT/RW, Kelurahan Government, and the National Police as law enforcers to curb the use of way outside the function.